Giulio Aleni's Xifang dawen (Questions and Answers on the West) and the Construction of the Image of Europe - LI, Le (Journal of Research for Christianity in China (JRCC), 2025)
Giulio Aleni's Xifang dawen was the first work in the Chinese world to systematically present Western customs and traditions. Its composition catered to the late Ming literati's fascination with foreign lands while also serving the Jesuits' need to project an image of Europe for the propagation of Christianity. During his research and writing, Giulio constructed an idealized image of Western European society, covering political systems, cultural education, and customs. He emphasized Christianity's political efficacy and its positive influence on customs, inevitably introducing exaggeration and idealistic elements. Influenced by multiple factors, the book circulated primarily among Jesuit missionaries and believers in China. The image of Europe it presented was accepted only by a very small segment of scholars during the Ming and Qing dynasties.